Diagnostyka i leczenie zachowawcze łokcia tenisisty = Diagnosis and conservative treatment of tennis elbow - Wójcik, Gustaw; Stawińska, Teresa; Szulc, Anna; Sokołowska, Barbara (Journal of Education, Health and Sport, 2017)
Wójcik Gustaw, Stawińska Teresa, Szulc Anna, Sokołowska Barbara. Diagnostyka i leczenie zachowawcze łokcia tenisisty = Diagnosis and conservative treatment of tennis elbow. Journal of Education, Health and Sport. 2016;6(11):98-107. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.164191 http://ojs.ukw.edu.pl/index.php/johs/article/view/3969 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 31.10.2016. DIAGNOSTYKA I LECZENIE ZACHOWAWCZE ŁOKCIA TENISISTY DIAGNOSIS AND CONSERVATIVE TREATMENT OF TENNIS ELBOW Wójcik Gustaw1,2, Stawińska Teresa3, Szulc Anna3, Sokołowska Barbara1 1 Państwowa Szkoła Wyższa im. Papieża Jana Pawła II w Białej Podlaskiej, Wydział Nauk o Zdrowiu i Nauk Społecznych. 2 Uniwersytet Medyczny w Lublinie, Katedra Rehabilitacji, Fizjopterapii i Balneoterapii, Zakład Balneoterapii. 3 Uniwersytet Medyczny w Lublinie, Katedra Rehabilitacji, Fizjoterapii i Balneoterapii, Zakład Rehabilitacji. dr n. med. Wójcik Gustaw1,2 dr n. o zdr. Stawińska Teresa3 dr n. o zdr. Szulc Anna3 dr n. med. Sokołowska Barbara1 Słowa kluczowe: łokieć tenisisty, nadkłykieć boczny, tendinopatie STRESZCZENIE Wstęp Łokieć tenisisty jest stosunkowo częstym zaburzeniem układu mięśniowo-szkieletowego, dla którego skuteczna strategia leczenia jest nadal nieznana. Odpowiedzialny jest za znaczny ból i utratę funkcji chorej kończyny. Charakterystyczne dla schorzenia są degeneracyjne zmiany w strukturze kolagenu oraz nieprawidłowości w ukrwieniu związane z procesem neowaskularyzacji. Patologia jest wynikiem powtarzających się mikrourazów prowadzących do uszkodzenia tkanek. Czułość diagnostyki obrazowej zależna jest od czasu trwania schorzenia. Pierwszy okres choroby zazwyczaj wywoływany jest urazem, któremu może towarzyszyć stan zapalny, dlatego najbardziej skuteczną metodą leczenia może być terapia przeciwzapalna i unieruchomienie kończyny. Okres późniejszy to zmiany zwyrodnieniowe, a leczenie polega głównie na zwalczaniu bolesnych objawów. Stany oporne na leczenie zachowawcze kwalifikowane są do leczenia chirurgicznego. Cel pracy Przedstawienie aktualnej wiedzy na temat diagnostyki i leczenia entezopatii nadkłykcia bocznego kości ramiennej. Materiał i metody Praca oparta na przeglądzie piśmiennictwa z Baz PubMed, Scopus oraz Web of Science. Wnioski Podstawowym badaniem obrazowym w diagnostyce łokcia tenisisty jest badanie ultrasonograficzne. Klasyczna radiologia jest raczej wykorzystywana do różnicowania innych chorób dotyczących łokcia. Współczesne metody leczenia łokcia tenisisty oparte są na terapii zmian zwyrodnieniowych. Leczenie przeciwzapalne jest nieskuteczne w powyższej jednostce chorobowej. Key words: tennis elbow, lateral epicondylitis, tendinopathy ABSTRACT Introduction. Tennis elbow is a relatively common disorder of the musculoskeletal system, for which effective treatment strategy is still unknown. It is responsible for considerable pain and loss of function of the affected limb. Characteristic for the diseases are degenerative changes in the structure of collagen and abnormalities in blood supply associated with the process of neovascularization. Pathology is due to cycles of repetitive stress leading to tissue damage. The sensitivity of imaging depends on the duration of the disease. The first period of the disease is usually caused by trauma, which may be accompanied by inflammation, which is why the most effective treatment may be anti-inflammatory therapy and immobilization of a limb. The subsequent period is connected with degenerative changes, and treatment relies mainly on combating the painful symptoms. Conditions refractory to conservative treatment are eligible for surgery. The objective of the study. Presentation of current knowledge about diagnosis and treatment of enthesopathy of the lateral epicondyle of the humerus. Materials and method. The work is based on a review of literature of Baz PubMed, Scopus and Web of Science. Conclusions. The primary imaging technique for the diagnosis of tennis elbow is ultrasound. Classic radiology is rather used for the differentiation of other diseases related to the elbow. Modern methods of treatment of tennis elbow are based on the treatment of degenerative changes. Anti-inflammatory treatment is ineffective in the above disease.